Penerapan Teori Pembelajaran Behavior Guru Bimbingan Konseling Dalam Mencegah Terjadinya Bullying Terhadap Teman Di SMA Negeri 1 Sei Rampah - Aguswinarti, Eka; Nasution, Rusli Halil; Idris, Muhammad (STAI Tebing Tinggi Deli, 2024)
This research is a qualitative research. The type of this research uses a descriptive approach where this type of research is focused on answering research questions related to the questions of who, what, where and how an event or experience occurs until it is studied in depth to find patterns that appear in the event. In short, it can be explained that qualitative descriptive is a research method that moves on a simple qualitative approach with an inductive flow. This inductive flow means that qualitative descriptive research begins with an explanatory process or event which can finally be drawn a generalization which is a conclusion from the process or event. The purpose of this study is to find out how the strategy, planning, implementation and evaluation related to the guidance and counseling teacher (BK) strategy in preventing Bullying at SMA Negeri 1 Sei Rampah. Data collection used in this study was in the form of observation, interviews and documentation as well as other data that supports this study such as primary data and secondary data. Interview activities with teachers, principals and vice principals are data sources in the form of primary data. The results of this study's findings indicate that there are forms of Bullying actions in SMA Negeri 1 Sei Rampah such as calling friends by other inappropriate names, this is called verbal bullying. In addition, other forms of bullying were also found such as hitting, kicking or pushing friends on purpose, this form of action is called physical bullying. From this case, the strategy and role of the teacher are very much needed. The strategies used are to provide appropriate consequences, advise, and evaluate by finding out what factors cause bullying cases to occur.